Pharmacist-Led Digital Health Interventions for Patients with Diabetes: A Systematic Review - Christy A; Fernanda F; Insani WN; Abdulah R (Journal of Multidisciplinary Healthcare)
Alicia Christy,1,* Frisca Fernanda,1,* Widya Norma Insani,1,2 Rizky Abdulah1,2 1Department of Pharmacology and Clinical Pharmacy, Universitas Padjadjaran, Sumedang Regency, Jatinangor, Indonesia; 2Centre of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang Regency, Jatinangor, Indonesia*These authors contributed equally to this workCorrespondence: Widya Norma Insani, Department of Pharmacology and Clinical Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM 21, Jatinangor, West Java, 45363, Indonesia, Email widya.insani@unpad.ac.idAbstract: Digital health interventions have emerged as a promising approach for patient care. The aim of this study was to conduct a systematic review of pharmacist-led digital health interventions for patients with diabetes. The PubMed database was used to select randomized controlled trials that assess the effectiveness of digital health interventions on clinical outcomes among patients with type 1 and 2 diabetes from January 2005 to May 2024. We included randomized controlled trial (RCT) studies on type 1 and 2 diabetes mellitus, analyzing the effects of all digital health interventions by pharmacists, including telephone-based intervention, web-based intervention, and mobile health application, as compared to usual care. The outcomes were a reduction in HbA1c, changes in medication adherence, and reduction of adverse effects. We used the PRISMA reporting standard to implement and report the results. A total of 19 studies were included. Among these, the included digital health interventions were telephone monitoring (n = 15), web-based intervention (n = 2), mobile health application (n = 1), and text-message reminder (n = 1). The findings showed variability: around half of the studies (n = 10, 52.63%) indicated that patients receiving digital health interventions had reduced HbA1c levels compared to those receiving usual care, while five studies (26.31%) found no difference between the intervention and usual care. Five studies (26.31%) showed that such interventions increased medication adherence, while two studies (10.53%) found no difference when compared to standard care. Effectiveness of the intervention is related to several factors, including practicability and patient engagement, frequency of the intervention, and the provision of personalized communication. Tailoring interventions to individual patient profiles and providing adequate support for enhancing practicability of these tools may improve their effectiveness. Further research assessing the cost-effectiveness of such intervention is necessary to inform healthcare policy.Keywords: pharmacist, digital health intervention, diabetes, clinical outcomes, pharmaceutical care